« Montrez ce genre que je ne saurais voir ». Genre, sexualité et institutions dans la présidentielle de 2012 - Catherine Achin; Lucie Bargel (Genre, Sexualité et Société)
The article analyses what the 2012 presidential campaign reveals of gender and sexual issues in France. Based on the contributions gathered in this issue, it underlines at first the centrality of gender and sexuality as political language, central for staging the nation and the candidates’ strategic identities, which leads paradoxically to depoliticize certain issues. Second, the paper emphasizes on the power of presidential, heterosexual and partisan institutions in the (re) production of gender and sexual norms, within and beyond the political sphere.